Equality of Information on Women's Fiqh for Children with Special Needs in Banjarmasin: Kesetaraan Informasi Fiqih Perempuan Bagi Anak Berkebutuhan Khusus di Banjarmasin - Hafizah, Noor; Nuryadin, Nuryadin (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
Menstruation is an event that Allah SWT has ordained for women. It is important for every woman to understand menstruation because menstruation is directly related to thaharah, namely obligatory bathing which is a requirement for performing worship. This research aims to describe the equality of women's fiqh information for student with special needs in Banjarmasin, as well as identifying what factors influence it. This research uses a qualitative method with a descriptive approach. The subjects in this research are two female teachers who teach Islamic Education and Character subjects at SLB Negeri 2 Banjarmasin and SLB Negeri 3 Banjarmasin and the students are deaf children class XII, the object in this research is equality of information on women's fiqh for student with special needs in Banjarmasin. The results of the research show that information on women's fiqh about menstruation and obligatory bathing must be conveyed by teachers to deaf student in Islamic Education and Character subjects learning using sign language accompanied by oral narrative. The teacher also writes material about menstruation and obligatory bathing on the blackboard and uses video media to teach obligatory bathing procedures. There are several factors that influence the equality of women's fiqh information for children with special needs who are deaf, namely, first, the teacher or educator factor, there are teachers who do not master sign language so that they are constrained in conveying information, second, factors within the deaf child, namely the inability to receive auditory stimulation, language poverty, emotional instability and limited intelligence, and environmental factors, namely the family environment such as social support, understanding, and good interaction within the family.